2022
DOI: 10.1177/00110000221148219
|View full text |Cite
|
Sign up to set email alerts
|

Ways to Navigate Sexual Minority and Latter-day Saint Identities: A Latent Profile Analysis

Abstract: Using a sample of 815 sexual minorities (SMs) with current or historical engagement with the Church of Jesus Christ of Latter-day Saints, we examined (a) how many empirically distinct ways there are to navigate SM and religious identities and (b) whether these ways were related to health. A latent profile analysis, which grouped participants by religious/spiritual (i.e., religious commitment, service attendance, Christian orthodoxy) and SM identity (i.e., outness, identity centrality, sexuality support) variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Given the sensitive nature of discussing difficulties associated with clients’ identities, therapists have an ethical obligation not only to understand these identities but to help clients navigate these harmful struggles. Therapists (and the clients they serve) may benefit from familiarizing themselves with other literature on working with LDS SM clients (Lefevor, 2023; Lefevor, Meter, & Skidmore, 2023; Sorrell et al, 2024) as well as key support groups for LDS SMs such as Affirmation and North Star and podcasts for LDS SMs like Listen , learn , and love and Questions from the closet .…”
Section: Discussionmentioning
confidence: 99%
“…Given the sensitive nature of discussing difficulties associated with clients’ identities, therapists have an ethical obligation not only to understand these identities but to help clients navigate these harmful struggles. Therapists (and the clients they serve) may benefit from familiarizing themselves with other literature on working with LDS SM clients (Lefevor, 2023; Lefevor, Meter, & Skidmore, 2023; Sorrell et al, 2024) as well as key support groups for LDS SMs such as Affirmation and North Star and podcasts for LDS SMs like Listen , learn , and love and Questions from the closet .…”
Section: Discussionmentioning
confidence: 99%
“…However, Lefevor et al (2021b) found internalized homophobia related to depression for Latter-day Saints (unrelated for non-Latter-day Saints) though it was unrelated to life satisfaction for Latter-day Saints (it was related for non-Latter-day Saints). Lefevor et al (2022b) categorized their sample as engaged Latter-day Saints, moderately engaged Latter-day Saints, and lapsed Latter-day Saints, finding no differences in depression or life satisfaction across these groups but greater meaning of life and fewer alcohol problems for engaged Latter-day Saints.…”
Section: Sexual and Gender Minority Latter-day Saintsmentioning
confidence: 99%